Respuesta :

Answer:

x = 4,

y = 1

Step-by-step explanation:

Let us solve through elimination ~

1. Multiply top equation -2x - y = -9 by -2, adding that product to the bottom equation 5x - 2y = 18:

-2 (-2x - y = -9)     ⇒     4x + 2y = 18    

+  5x - 2y = 18         +    5x - 2y = 18

2. To further express this algebraic process of adding to find x in this case:

     4x + 2y = 18        ⇒     9x = 36     ⇒     x = 4

+    5x - 2y = 18

3. Now let us substitute this value of x into the top equation 4x + 2y = 18:

4( 4 ) + 2y = 18    

4. And solve for y:

16 + 2y = 18    ⇒   2y = 2   ⇒    y = 1